International organizations’ activities in rescue of European Jews during the Holocaust: personal dimension - Radchenko, Iryna G. (Journal of the Belarusian State University. History, 2018)
The article is devoted to the international organizations’ activities in rescue the Jewish population of Europe during the Holocaust through the prism of representatives of these organizations. Thanks to the personal approach, humanitarian missions of the international community aimed at saving European Jewry are reviewed and analyzed. Materials from the leading American archives, the latest literature for research of identities of the international institutions’ representatives are involved. Little-known facts about the activities of organizations’ certain representatives regarding the salvation of the Jewish population in European countries are revealed. Chronological stages, during which the humanitarian activity of international organizations’ representatives was carried out, has been indicated and characterized. It was revealed that aid and rescue for the affected Jewish population of Europe came during the entire period of the Holocaust, but the most active rescue of Jews began in the last period of the war (1944–1945), when it became possible to engage all international institutions, diplomatic missions for the organization of the process of rescue.
Keywords: Holocaust; personality; international organization; rescue; humanitarian mission; European Jewry